Hands-On Deep Learning Architectures with Python : Create deep neural networks to solve computational problems using TensorFlow and Keras /: Create deep neural networks to solve computational problems using TensorFlow and Keras. (2019) - Liu, Yuxi (Hayden); Mehta, Saransh
No abstract available